@highschoolmom2010
In the seventh response after you posted the figure at the top, I wrote:
"Divide the long leg by sqrt(3) to get the short leg, x.
Then multiply the short leg by 2 to get the hypotenuse, y."
Then I had to leave. I thought I was pretty much telling you exactly what to do to solve this problem, but maybe you didn't understand.
To find x:
"Divide the long leg by sqrt(3) to get the short leg, x." means:
\( x = \dfrac { 2 \sqrt{3} } {\sqrt{3}}\) (the \(\sqrt{3} \) in the numerator and the \(\sqrt{3}\) in the denominator cancel out, so
\(x = 2\)
To find y:
"Then multiply the short leg by 2 to get the hypotenuse, y"
\(y = 2 \times 2\)
\(y = 4\)
BTW, above you wrote your answer as "so x=4 and y=2 ", but you switched the values of x and y.